Moderate Islamic Influencers in Digital Communication Discourse - Musta'in, Musta'in (Communicatus: Jurnal Ilmu komunikasi, 2022)
This research aims to explain the digital communication patterns carried out by religious influencers in transmitting and distributing Islamic values as a representation of moderate Islam, with Habib Ja'far as the central figure. The data used in this qualitative study was gathered by looking at the YouTube login account of a channel that Onadio Leonardo and Habib Ja'far lead. Research data analysis refers to the concept of digital communication developed by Caroline Tagg, which emphasizes flexibility, freedom, and dialogue in digital interactions. The research results show that, first, in the new media era, content uploaded by the login account has become a strategic medium for conveying moderate Islamic values by utilizing an inclusive approach using relaxed, humorous, and engaging language. Second, Habib Ja'far, as a religious influencer, prioritizes the spirit of freedom of communication, namely the expression of religious beliefs that not only respect differences but also avoid blaming or denigrating other beliefs. This approach shows that Islam can be presented as a friendly, tolerant religion relevant to the times' challenges. This research contributes to understanding the role of digital communication in voicing Islamic values of moderation. These findings also offer a new perspective on how digital media can be a strategic space for conveying peaceful and inclusive Islamic narratives.